ENT 530 Social Media Portfolio: Syufa Owlwear / Nur Syuhada Mohd Aris - Mohd Aris, Nur Syuhada (2021)
SYUFA OWLWEAR is the combination between my name and my friend name because my friend is the owner of this business and I just her business partner. On the beginning, we started this business just for fun because at that time we feel like wanted to try something new. Furthermore, we feel so bored staying at home without doing anything. SYUFA OWLWEAR provide all kinds of clothes such as knitwear, blouse, and Muslimah Clothes. We offer affordable price to our customers based on what clothes that they prefer to buy that they think suitable for them. Our target customers are a group of people who really like knitwear, blouse, and Muslimah Clothes at a lower cost and need any option of different colours and style so they can make their own choice, so it will meet their preferences. We give a best service to our customer so that, they will feel satisfied with our performance. We started our business in March 2018, which we give a long thought on what we should sell for our business. Then we make a Go-Ecommerce registration. We started our business with selling knitwear, blouse, and now we only focus on selling Muslimah Clothes. We offer an affordable price to our customers. Our slogan which is “KEEP FASHION IN THE BEST STYLE” means, although we wear a cheapest and normal style, but we still can keep it with the best style that we like. So, most of our customer satisfied with our service. At the moment, SYUFA OWLWEAR only owned and work by my friend, Nur Fatin Syamimi bt Mohd Zaid because I could not help her yet due to I further my study, and I will help her in business during semester break by promoting our business and being her business partner. It is my dream to run a business with her as our part time hobby. Before I started using FACEBOOK as our platform, we are using WhatsApp story, Instagram and Shoppe as our platform to attract online customers by posting and promote our business. Using FACEBOOK platform, we can promote SYUFA OWLWEAR by doing teaser post, soft cell, and hard cell as our sale postings, so we can attract more customers to visit our store in FACEBOOK Pages and Shoppe.